2003
DOI: 10.1097/01.ju.0000091873.09677.f4
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Gene Amplification and Protein Expression in Recurrent Prostate Cancer

Abstract: AR amplification in recurrent prostate cancer results in higher levels of AR protein expression but does not affect survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 10 publications
8
87
1
1
Order By: Relevance
“…Constitutively high AR expression has been found in hormone refractory tumors, but lower expression of the AR was noted during regression of hormonally treated PCa. 21,22,[27][28][29][30] AR amplification may contribute to its own activation in a relative absence of androgens; moreover, AR appears to undergo structural and functional alterations during PCa progression. We have previously observed that bicalutamide is able to inhibit significantly and dose-dependently the proliferation of established AR-positive human PCa cell lines and of primary cultures of PCa cells obtained directly from clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…Constitutively high AR expression has been found in hormone refractory tumors, but lower expression of the AR was noted during regression of hormonally treated PCa. 21,22,[27][28][29][30] AR amplification may contribute to its own activation in a relative absence of androgens; moreover, AR appears to undergo structural and functional alterations during PCa progression. We have previously observed that bicalutamide is able to inhibit significantly and dose-dependently the proliferation of established AR-positive human PCa cell lines and of primary cultures of PCa cells obtained directly from clinical samples.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the situation in hormone refractory PCa cells found in specimens obtained from patients, there is evidence that these cells have upregulated hAR mRNA (Gil-Diez de Medina et al, 1998;Latil et al, 2001) as well as hAR protein (Ford et al, 2003). Similar findings are also reported for human PCa cell xenografts (Chen et al, 2004a) and cultured PCa cells that are chronically deprived of androgen (Shi et al, 2004).…”
Section: Discussionmentioning
confidence: 73%
“…This conundrum has led to extensive research to determine mechanisms through which androgen signaling might be maintained in PCa cells in hormone-treated patients. Various studies reveal that there are likely multiple pathways leading to increased androgen signaling in a low androgen environment involving mechanisms as diverse as hAR gene amplification (Ford et al, 2003), mutations that alter the ligand specificity of the hAR (Tilley et al, 1996) or by association of the hAR protein with coactivators that cooperate to increase transcriptional activity of hAR (Rahman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…19 The expression of AR protein in tumors with amplification has been reported to be high. 18,25 However, it was also seen that although protein expression was increased in 80% of HR tumors with amplification, tumors without amplification also showed an increase in protein expression 25 as seen in the case of mRNA expression. Amplification has also been correlated to PSA expression and survival.…”
Section: Amplification Of the Armentioning
confidence: 88%
“…16,17 Amplification of the AR gene was seen in approximately 20-30% of all HR tumors. [18][19][20][21][22][23] In addition, there was heterogeneity in the amplification seen within tumors. 22 These studies indicated that since amplification is seen in refractory tumors, only the clones having the amplifications would be selected for further growth in a low-androgen environment, and would accumulate the chromosomal changes with time to establish aggressive disease.…”
Section: Amplification Of the Armentioning
confidence: 99%